Response of bacterial community to iron oxide nanoparticles during agricultural waste composting and driving factors analysis. (February 2022) - Zhang, Lihua; Hu, Yunlong; Huang, Hongli; Ren, Liheng; Zhang, Jiachao; Yan, Binghua; Luo, Lin; Liu, Jun; Gu, Sijia
Highlights: The succession of bacterial community and their metabolic function were studied. The abundances of dominant genera varied due to FeONPs treatments. The core genera for OM and WSC changes were different among three treatments. FeONPs promoted the metabolism of amino acids. FeONPs altered driving factors for bacterial community and metabolism succession. Abstract: The succession of bacterial communities and their function, and the core microorganisms for water soluble organic carbon (WSC) and organic matter (OM) changes during agricultural waste composting with addition of iron oxide nanomaterials (FeONPs, Fe2 O3 NPs and Fe3 O4 NPs) were investigated. Moreover, driving factors for bacterial composition and metabolism were analyzed. Results showed that FeONPs treatments increased the relative abundance of thermophilic microorganisms for OM degradation. Most of the core genera were responsible for decomposition of OM and synthesis of WSC. Additionally, FeONPs promoted the metabolism of amino acids. The most significant factors for dominant genera in control, Fe2 O3 NPs and Fe3 O4 NPs group were moisture (62.1%), moisture (62.0%) and OM (58.2%), respectively. For metabolism, the most significant factors in control, Fe2 O3 NPs and Fe3 O4 NPs group were temperature (57.2%), NO3 – -N (60.5%), NO3 – -N (62.6%), respectively. The relationships between compost properties, bacterial community and metabolism were changed by FeONPs.